Consumption of coffee and tea and risk of developing stroke, dementia, and poststroke dementia: A cohort study in the UK Biobank - Yuan Zhang (Public Library of Science (PLoS), 2021)
Background Previous studies have revealed the involvement of coffee and tea in the development of stroke and dementia. However, little is known about the association between the combination of coffee and tea and the risk of stroke, dementia, and poststroke dementia. Therefore, we aimed to investigate the associations of coffee and tea separately and in combination with the risk of developing stroke and dementia. Methods and findings This prospective cohort study included 365,682 participants (50 to 74 years old) from the UK Biobank. Participants joined the study from 2006 to 2010 and were followed up until 2020. We used Cox proportional hazards models to estimate the associations between coffee/tea consumption and incident stroke and dementia, adjusting for sex, age, ethnicity, qualification, income, body mass index (BMI), physical activity, alcohol status, smoking status, diet pattern, consumption of sugar-sweetened beverages, high-density lipoprotein (HDL), low-density lipoprotein (LDL), history of cancer, history of diabetes, history of cardiovascular arterial disease (CAD), and hypertension. Coffee and tea consumption was assessed at baseline. During a median follow-up of 11.4 years for new onset disease, 5,079 participants developed dementia, and 10,053 participants developed stroke. The associations of coffee and tea with stroke and dementia were nonlinear (P for nonlinear <0.01), and coffee intake of 2 to 3 cups/d or tea intake of 3 to 5 cups/d or their combination intake of 4 to 6 cups/d were linked with the lowest hazard ratio (HR) of incident stroke and dementia. Compared with those who did not drink tea and coffee, drinking 2 to 3 cups of coffee and 2 to 3 cups of tea per day was associated with a 32% (HR 0.68, 95% CI, 0.59 to 0.79; P < 0.001) lower risk of stroke and a 28% (HR, 0.72, 95% CI, 0.59 to 0.89; P = 0.002) lower risk of dementia. Moreover, the combination of coffee and tea consumption was associated with lower risk of ischemic stroke and vascular dementia. Additionally, the combination of tea and coffee was associated with a lower risk of poststroke dementia, with the lowest risk of incident poststroke dementia at a daily consumption level of 3 to 6 cups of coffee and tea (HR, 0.52, 95% CI, 0.32 to 0.83; P = 0.007). The main limitations were that coffee and tea intake was self-reported at baseline and may not reflect long-term consumption patterns, unmeasured confounders in observational studies may result in biased effect estimates, and UK Biobank participants are not representative of the whole United Kingdom population. Conclusions We found that drinking coffee and tea separately or in combination were associated with lower risk of stroke and dementia. Intake of coffee alone or in combination with tea was associated with lower risk of poststroke dementia. In a cohort study, Yuan Zhang and colleagues investigate the associations between coffee and tea consumption and risk of stroke and dementia among participants older than 50 years of age in the UK Biobank. Author summary Why was this study done? Stroke and dementia become an increasing global health concern and bring a heavy economic and social burden worldwide. Considerable controversy exists on the association of coffee and tea consumption with stroke and dementia. Little is known about the association between the combination of tea and coffee and the risk of stroke and dementia and poststroke dementia. What did the researchers do and find? This study included 365,682 participants (50 to 74 years old) from the UK Biobank who reported their coffee and tea consumption. We found that coffee intake of 2 to 3 cups/d or tea intake of 3 to 5 cups/d or their combination intake of 4 to 6 cups/d were linked with the lowest hazard ratio (HR) of incident stroke and dementia. Drinking 2 to 3 cups of coffee with 2 to 3 cups of tea daily were associated with a 32% lower risk of stroke and a 28% lower risk of dementia. Intake of coffee alone or in combination with tea was associated with lower risk of poststroke dementia. What do these findings mean? These findings highlight a potential beneficial relationship between coffee and tea consumption and risk of stroke, dementia, and poststroke dementia, although causality cannot be inferred. These findings may be of interest to clinicians involved in the prevention and treatment of stroke, dementia, and poststroke dementia.